2006
DOI: 10.1128/jcm.44.5.1650-1658.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Requirements and Antibiotic Resistance Patterns ofHelicobacterSpecies in Chemically Defined Media

Abstract: The growth of the gastric pathogen Helicobacter pylori in the absence of serum remains challenging, and nutritional requirements have only partially been defined, while almost nothing is known about nutritional requirements of other Helicobacter spp. Although previous data showed that H. pylori grows in the chemically defined medium F-12, but not in other tissue culture media examined, the specific components responsible for growth were not entirely understood. Here we describe the optimization of amino acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 26 publications
(30 reference statements)
5
81
0
1
Order By: Relevance
“…H. pylori requires zinc for growth in vitro (Testerman et al, 2001(Testerman et al, , 2006. We do not know whether zinc is limiting in the stomach, but studies have found that H. pylori infection lowers mucosal zinc concentrations (Sempértegui et al, 2007), possibly due to the presence of neutrophils, which produce the zinc-chelating agent calprotectin (Kehl-Fie & Skaar, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori requires zinc for growth in vitro (Testerman et al, 2001(Testerman et al, , 2006. We do not know whether zinc is limiting in the stomach, but studies have found that H. pylori infection lowers mucosal zinc concentrations (Sempértegui et al, 2007), possibly due to the presence of neutrophils, which produce the zinc-chelating agent calprotectin (Kehl-Fie & Skaar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…pylori does not require additional nickel for growth (Testerman et al, 2001(Testerman et al, , 2006, although it requires nickel as a cofactor for two critical enzymes: urease, which mediates pH homeostasis, and hydrogenase, which is used for hydrogen metabolism . The basal level of nickel in the medium is apparently sufficient for these enzymes, but it is not yet known whether in vivo nickel is limiting or toxic.…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded as a major etiologic factor in the development of chronic gastritis, peptic ulcer and gastric cancer (Lopez-Saez et al, 2010). In more detail, H. pylori are the main risk factor in 65-80% of gastric cancers, but in only 2% of such infections (You et al, 2000;Testerman et al, 2006;Vilchis et al, 2009;Janjetic et al, 2010;Zamani et al, 2011). That is to say, despite the worldwide distribution of H pylori infection in patients with gastric disease, only a few number of infected individuals develop gastric cancer, It is important to clarify other factors that may determine risk among those infected with H. pylori (Hisaki et al, 1988;Lin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was more recently shown that purines are required for growth in Reynolds and Penn's defined medium for strain G27 (17), and that catalase was incapable of restoring growth in purine-free media. Similar studies utilizing the tissue culture medium Ham's F12 and subsequent derivations have also shown that purines are essential for the growth of H. pylori strain 26695 (18,19), and this has been recently reconfirmed by researchers utilizing a series of mutants for purine nucleotide metabolism (20,21).…”
mentioning
confidence: 89%